The occurrence and phenology of moth pests in different granary of Borsod-Abaúj-Zemplén County - Görcsös, Gábor; Bozsik, András (Acta Agraria Debreceniensis, 2010)
The aims of my studies were the followings: primarily to find correlation between the conditions of granary and the occurrence of moth pests. Secondly I studied the effect of disinfection on individual numbers in the population of moths. My studies were started in May 2009 in six different places of Borsod-Abaúj-Zemplén County. Indianmeal moth (Plodia interpunctella) and Mediterranean Flour Moth (Ephestia kuehniella) traps with pheromone were installed in four repetitions as well as Angoumois Grain Moth (Sitotroga cerealella) traps in also four repetitions. Control traps without attractant were also placed at every place.From my researches, it became clear that the disinfection alone is not enough to protect cereals from moths. As in the case of crop protection, we need to apply integrated pest management.We have to make differences between preventive protections from moth pests and the elimination of them by chemicals.Up to my opinion, the regular checking and cleaning of the granary are important as well as the prognosis of the possible occurrence of moths. The prognosis is considered important because the studied moths do not feed at the adult stage or only at a low level. However, the caterpillars coming from the eggs placed by females can cause a significant damage in the stored cereals.The studied sex pheromone traps are proved to be useful for the reduction of number of moths since the traps caught lots of them. These traps are relatively cheap because only the temporarily changes of pheromones increase the cost.